Comparative effectiveness of ACE inhibitors and angiotensin receptor blockers in patients with prior myocardial infarction. Issue 1 (4th May 2019) - Ko, Dennis; Azizi, Paymon; Koh, Maria; Chong, Alice; Austin, Peter; Stukel, Therese; Jackevicius, Cynthia
Abstract : Objective: Although ACE inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are commonly prescribed for patients with coronary artery disease, whether these medications are similarly effective is still a subject of intense debate. Our objective was to compare the clinical effectiveness of ACEIs and ARBs in patients with prior myocardial infarction (MI). Methods: All residents older than 65 years, alive on 1 April 2012, with a prior MI were included. Propensity weighting was used to balance potentially confounding baseline covariates between the treatment groups. The primary outcome was a composite of cardiovascular death, hospitalisation for MI or unstable angina at 3 years. Results: Our cohort included 59 353 patients with MI; their mean age was 77 years and 40% were women. In the propensity-weighted cohort, the primary outcome occurred in 6.5% in the ACEI group and 5.7% in the ARB group at 1 year (HR comparing ACEI with ARB 1.14, 95% CI 1.05 to 1.23, p<0.001). At 3 years, the primary outcome occurring in 16.0% with ACEIs and 15.1% with ARBs (HR 1.07; 95% CI 1.02 to 1.12; p<0.001). A significant interaction with sex was observed, with women prescribed ACEIs having a higher hazards (HR 1.17; 95% CI 1.10 to 1.26) compared with ARBs, while no significant difference was seen among men (HR 1.00; 95% CI 0.93 to 1.06, interaction p<0.001). Conclusions: Despite previous concerns regarding ARBs, we found that they had slightly lower rates of adverse clinical cardiovascular outcomes among older patients with MI compared with ACEIs. The observed difference in clinical outcomes may be related to a sex difference in effectiveness.